Optimizing Lombok’s Pearl Industry: The Role of Social Media and Fintech in Enhancing SME Business Performance through Competitive Advantage - Indra Gunawan; Wiwik Handayani; Nanik Hariyana (Universitas Negeri Semarang, 2024)
Utilizing digital technology in business enhances competitive advantage, significantly improving performance, particularly for small and medium firms. (UKM). This study seeks to investigate the impact of social media marketing and the integration of financial technology (FinTech) on company performance, with competitive advantage serving as a mediating variable within the small and medium-sized companies (SMEs) of the Lombok pearl sector. The study methodology employs a quantitative approach utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The research sample comprises 120 players in the Lombok pearl industry SMEs utilizing social media marketing and finance technology, selected via the census technique through the SME association. The research findings indicate that social media marketing does not immediately boost company performance; nonetheless, it greatly adds to the augmentation of competitive advantage, which subsequently enhances business performance. The implementation of financial technology significantly influences corporate performance and enhances competitive advantage. Moreover, competitive advantage has demonstrated its role as a mediating variable that enhances the association between social media marketing and the adoption of financial technology in relation to company success.